2021
DOI: 10.1111/etho.12320
|View full text |Cite
|
Sign up to set email alerts
|

The Melancholy of Bones: Forensic Exhumation as an Elegiac Transformative Experience

Abstract: Since the early 1990s, forensic exhumation of mass graves in the wake of violent conflict has become an increasingly important humanitarian intervention. Exhumation has two stated aims: to document evidence of atrocity for judicial proceedings and to return bodies to families to bring psychological closure. Exhumation is premised on the idea that opening graves bring mourners’ closure, but little research has been done to examine how humanitarian exhumation affects the families of the missing. In this article,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This data is similar to other third world countries and signifies the fact that most of these deaths may have occurred due to unplanned assault. 17,18 In contrast, Qazi et al (2019) found that blunt head and chest traumas accounted for the majority of fatalities (71.9%). 23 Finally, speaking of the most important aspect of this study we observed that more than half of the bodies exhumed were partially decomposed over 40% were in advanced decomposed state.…”
Section: Discussionmentioning
confidence: 97%
“…This data is similar to other third world countries and signifies the fact that most of these deaths may have occurred due to unplanned assault. 17,18 In contrast, Qazi et al (2019) found that blunt head and chest traumas accounted for the majority of fatalities (71.9%). 23 Finally, speaking of the most important aspect of this study we observed that more than half of the bodies exhumed were partially decomposed over 40% were in advanced decomposed state.…”
Section: Discussionmentioning
confidence: 97%